2009
DOI: 10.4049/jimmunol.0802113
|View full text |Cite
|
Sign up to set email alerts
|

Chitin Is a Size-Dependent Regulator of Macrophage TNF and IL-10 Production

Abstract: Chitin is a ubiquitous polysaccharide in fungi, insects, and parasites. We hypothesized that chitin is a size-dependent regulator of innate immunity. To test this hypothesis, we characterized the effects of chitins of different sizes on murine bronchoalveolar or peritoneal macrophages. In these studies, large chitin fragments were inert, while both intermediate-sized chitin (40–70 μm) and small chitin (SC; <40 μm, largely 2–10 μm) stimulated TNF elaboration. In contrast, only SC induced IL-10 elaboratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
242
5
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(262 citation statements)
references
References 34 publications
12
242
5
3
Order By: Relevance
“…It has also been shown that the size of chitosan was important for phagocytosis (19,20). In fact, the differential role of the size of chitin was supported by another report (21). In our system, chitosan indeed seemed to induce more IL-1β production than chitin in vitro, probably due to the easier accessibility of chitosan to the cells, which might derive from the different solubility between chitin and chitosan, but chitin itself also significantly induced IL-1β ( Fig.…”
Section: Chitin Uncleaved By Enzymatically Dead Amcase Is Not Phagocysupporting
confidence: 72%
See 3 more Smart Citations
“…It has also been shown that the size of chitosan was important for phagocytosis (19,20). In fact, the differential role of the size of chitin was supported by another report (21). In our system, chitosan indeed seemed to induce more IL-1β production than chitin in vitro, probably due to the easier accessibility of chitosan to the cells, which might derive from the different solubility between chitin and chitosan, but chitin itself also significantly induced IL-1β ( Fig.…”
Section: Chitin Uncleaved By Enzymatically Dead Amcase Is Not Phagocysupporting
confidence: 72%
“…It is interesting that chitins of different sizes have different effects both in vivo and in vitro (19,21). It was previously reported that intranasal administration of chitin beads induced infiltration of IL-4-expressing cells in lung, but administration of chitin beads that were pretreated with recombinant AMCase failed to induce infiltration of IL-4-expressing cells in lung (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most published studies on chitin and chitosan used preparations derived from crustacean sources (16,20), as in our studies, although some have used chitin isolated from fungi (19,38). There are known structural differences between the two sources (39) that could have an impact on how the particles effect the immunological response.…”
Section: Discussionmentioning
confidence: 96%